Design of computerized drug delivery control systems - Lu, Shan. (2008)
A fuzzy controller-based multiple-model adaptive control system (FCMMAC) for drug delivery control system was presented in this report. We developed a multiple-model adaptive control (MMAC) algorithm to identify the patient model, because the transfer function parameters were different for each patient and variant with time, and it was shown that such an algorithm was desirable for maintaining both steady-state and transient specifications [1]. Additionally, we used a fuzzy control (FC) method to design a controller bank for blood pressure control; in fact, each fuzzy controller in the controller bank was a nonlinear proportional-integral (PI) controller whose proportional gain and integral gain adjusted continuously according to error and rate change of error of the process output [2].